KORUPSI DALAM PERSPEKTIF HADIS AHKAM (Studi Kritis pada Sanad dan Matan Hadis) - Saidah, Saidah (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri (IAIN) Parepare, 2015)
The issue of corruption can’t be eradicated optimally in a Muslim -majority country where the issue is poorly understood and realized the danger, according to some traditions as a source of Islamic law. Therefore, this article seeks to examine critically the prohibition of corruption according to law tradition. With reference to the hadith of corruption could serve as the basis of law (hujjah) as having a legitimate level of quality both in terms of sanad and matan tradition. Either textually or contextually, fill in the content of the hadith narrated by Imam al-Darimiy core of the prohibition to perform acts of corruption, abuse of authority or mandate either squandered that trust comes from a particular person or government agencies .